PRINSIP AL-TAYSĪR DALAM FIQH AL-AQALLIYĀT YŪSUF AL-QARAḌĀWĪ - Khalil, Abdul Wahab (STAIN Kediri, 2016)
The Muslim minorities in the West who are currently dealing with a multitude of problem receives attention from Muslim scholars. Syaikh Yūsuf al-Qaraḍāwī is the first Muslim scholar who attempted to provide a solution to the problems, especially related to the implementation of religious teachings, as he outlined it in the framework of fiqh al-aqalliyāt. In principle, this is not something new in Islamic jurisprudence, because its legal sources are still the same. Nevertheless, this kind of fiqh is different in the sense that it does not merely talk about legal issues, but also the problems of theology and morals that the Muslim minorities in the West are currently dealing with in their relations with non-Muslims. Fiqh al-aqalliyyāt is also characterized by the use of the principle of al-taysīr as clearly prominent in the fatwās by Syaikh Yūsuf al-Qaraḍāwī, such as on the validity of both performing Friday prayer in the morning due to limited time for religious sermon (khuṭbah) and during ẓuhr time in some countries. This article will explore further this principle of al-taysīr in the Qaraḍāwī’s fiqh al-aqalliyyāt. Keywords: Yūsuf al-Qaraḍāwī, Fiqh al-Aqalliyāt, al-Taysīr